Feasibility study of margarine substitute based on gelatin-oil emulsion gel - Wipawan Kangchai (Science Faculty of Chiang Mai University, 2019)
With increasing of consumer health concern, margarine substitute is recently received more attention from food industry in order to avoid bad fatty acids, i.e., trans- and saturated fatty acids. One approach to serve such requirement involves emulsion design and hydrocolloid structuring agent. Therefore, in this study, emulsion gels with gelatin as a structuring agent were prepared to access the possibility of preparing low-fat margarine substitute. Various parameters such as gel strengths (100, 150, 200 and 250 bloom values) and concentrations (6 and 10%w/w) of gelatin, types (soybean, rice bran, and canola) and contents (10-30% w/w) of vegetable oil influencing textural properties and microstructure of the prepared emulsion gels were investigated. The results showed that gel strength in term of Young’ s modulus of gelatin gels ranging from 10.38 to 36.75 kPa was directly proportion to their bloom values. It was also found that gelatin concentration and bloom strength noticeably affect the textural properties and microstructure of the emulsion gels. Furthermore, the textural properties of the emulsion gels depended on vegetable oil type and content. Among the studied vegetable oils, gelatin-oil emulsion gel formulated from rice bran oil exhibited the textural properties, especially firmness and stickiness, comparable to commercial margarine. With exception of adhesiveness, firmness, spreadability, and stickiness of the samples also slightly increased with increasing of oil content.